Just a phrase I'm going through [ my life in language - Crystal, David , 1941- (Routledge, 2009)
"... reflecting on a long and hugely successful career at the forefront of the field of English language and linguistics, David Crystal answers this question and offers us a special look behind the scenes at the adventures, rewards, challenges and pitfalls of his life in language."